DIMENSIKUALITATIF KEBERHASILAN PERLUASAN KESEMPATAN KERJA - Haryo Kuncoro (Faculty of Economics and Business, Universitas Gadjah Mada, 1999)
People argue that employment is concerned with the numerical matters. This isbecause any discussion about employment problems always refers to the quantitativedata such as labor force, employment opportunities, and the most important figure isopen unemployment rate. Therefore, the employment problems are presumablyidentical to create the jobs widely. However, stressing merely on the quantitativeaspects is quite risky to understand the employment problems completely.This article attempts to identify some qualitative aspects in evaluating thesuccess of the jobs creation. Based on the conceptual analysis proposed, weconcluded that creating the jobs as much as possible is necessary condition but notsufficient to achieve the goals of economic development. It means that the governmentshould consider not only the quantitative aspects but also the qualitative aspects.Indeed, the employment is one of the greatest obstacles for any government in theworld.